Project Based Learning Based E-book Kvisoft Flipbook Maker for Grade V Elementary School - Kharisna, Feby; Risda Amini (MIMBAR PGSD Undiksha, 2023)
Currently, there are still many teachers who still need to utilize technology optimally. Based on this, the research objective was to develop a PjBL-based e-book assisted by the Ubisoft flipbook maker in grade V of elementary school. This type of research uses Research and Development (R&D) with the ADDIE Development Model. The data obtained in this study were obtained from observations, interviews and tests. The instrument used in collecting data is a questionnaire. Five validators carried out a validity assessment. Effectiveness test involving 35 students. The data analysis technique is descriptive qualitative and quantitative analysis. The research results show that the language validity value is 79.33 (Valid). The mean view validity is 80.20 (Valid). Graphical validity is 86.00 (very valid). Material validity is 82.42 (Valid). The result of the teacher's response was 83.33 (practical). The results of student responses were 85.95 (very practical). The effectiveness test showed good results, namely the average value of 82.93 (very good). It was concluded that the PjBL-based book, assisted by the Ubisoft flipbook maker, is feasible and effective for elementary school students learning.